2004
DOI: 10.1111/j.1365-2109.2004.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of planktonic sea lice larvae Lepeophtheirus salmonis in the inter-tidal zone in Loch Torridon, Western Scotland in relation to salmon farm production cycles

Abstract: This study examines the relative density of sea lice, Lepeophtheirus salmonis (Krøyer), larvae in the inter‐tidal areas of Loch Torridon, a fjordic sea loch in Western Scotland and the site of several commercial salmon farms. Samples of planktonic sea lice were collected in each spring from 1999 to 2003 near the mouth of the River Shieldaig, where sea trout have been shown to congregate in the first few days after going to sea, and from 2001 to 2003 near the mouth of the River Balgy. No larval sea lice were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 25 publications
6
52
1
Order By: Relevance
“…This correlation indicates that the gravid L. salmonis on the farmed salmon were an important source of sea louse larvae. Plankton surveys have suggested that larval Lepeophtheirus salmonis can be carried several kilometres landward from their source (McKibben & Hay 2004a, Penston et al 2004, and this suggestion is supported by numerical models (Asplin et al 2004, Murray & Gillibrand 2006, Gillibrand & Willis 2007. This implies that self-sustaining L. salmonis populations on farms (Tully 1989, Bron et al 1993a,b, Jackson et al 1997, Revie et al 2005) might be contributing to infestation pressure in the wider environment, not just in their immediate vicinity.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…This correlation indicates that the gravid L. salmonis on the farmed salmon were an important source of sea louse larvae. Plankton surveys have suggested that larval Lepeophtheirus salmonis can be carried several kilometres landward from their source (McKibben & Hay 2004a, Penston et al 2004, and this suggestion is supported by numerical models (Asplin et al 2004, Murray & Gillibrand 2006, Gillibrand & Willis 2007. This implies that self-sustaining L. salmonis populations on farms (Tully 1989, Bron et al 1993a,b, Jackson et al 1997, Revie et al 2005) might be contributing to infestation pressure in the wider environment, not just in their immediate vicinity.…”
mentioning
confidence: 55%
“…However, because the identity of the nauplii is presumptive, we shall refer to the nauplii generically as 'sea louse nauplii'. Previous plankton surveys in Loch Shieldaig also found L. salmonis to be the predominant louse species (McKibben & Hay 2004a, Penston et al 2008. Larval L. salmonis densities were significantly lower for a large part of Cycle 2 compared to Cycle 1.…”
Section: Discussionmentioning
confidence: 95%
“…Experiments in the laboratory and sea pens have shown that L. salmonis copepodites swim upwards towards light and do not cross into low salinity waters (Heuch 1995;Heuch et al 1995;Bricknell et al 2006). Plankton sampling discovered higher densities of L. salmonis copepodites in very shallow water along the seashore and in estuarine areas of Ireland and Scotland (Costelloe et al 1995(Costelloe et al , 1998McKibben & Hay 2004). While the same copepodite distribution may be expected in British Columbia, it requires confirmation because the Pacific and Atlantic populations of L. salmonis are genetically distinct (Tjensvoll et al 2006;Todd et al 2006) and may have different evolutionary adaptations.…”
Section: Research Progress (A) Larval Dispersal and Transportmentioning
confidence: 99%
“…Temporal patterns in the abundance of planktonic L. salmonis nauplii and copepodids in coastal and off-shore regions of a Scottish loch are correlated with treatment or relocation actions of farmed salmon within the same loch (McKibben & Hay 2004, Penston et al 2008, Penston & Davies 2009. Similarly, infection pressure on sentinel salmon smolts is related to the abundance of ovigerous L. salmonis on adjacent populations of cultured salmon (Bjørn et al 2011, Pert et al 2014.…”
Section: Mitigating Factors and Spillbackmentioning
confidence: 99%